Gli accessi chirurgici alla spalla - De Biase, P.; Biancalani, E.; Cortonesi, G.; Martinelli, D. (Lo Scalpello - Journal, 2018)
SURGICAL APPROACH TO PROXIMAL HUMERUS The shoulder’s traumatology in recent decades has seen a major increase in surgical compared to conservative treatment even if recent studies and meta-analyzes do not confirmed that surgical treatment leads to better functional results. The interest in the surgical accesses, expecially in mininvasive surgery, for the treatment of fractures of the proximal humerus had a new birth. The aim of this work is to illustrate the most commonly used surgical technique in traumatology of proximal humerus.